2022
DOI: 10.3390/jcm11143992
|View full text |Cite
|
Sign up to set email alerts
|

Living with Advanced Breast Cancer: A Descriptive Analysis of Survivorship Strategies

Abstract: Survivors of advanced breast cancer (ABC), also known as metavivors, are often left with fewer treatment options in the landscape of a cure culture. Metavivors have unique psychosocial and physical needs distinct from patients with early-stage breast cancer. This analysis delves into side effects commonly experienced by patients with ABC, such as fatigue, anxiety, and cardiotoxicity; how these side effects impact caregiver support, financial toxicity, emotional strain, and spiritual and emotional distress; as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…[ 5,6 ] Breast cancer patients initially respond well to chemotherapy, but drug‐resistant breast cancer cells usually readily emerge after long exposure to chemotherapeutics, resulting in treatment failure. [ 7,8 ] Moreover, advanced breast cancer with distant metastases is incurable with currently available chemotherapeutics, [ 9,10 ] and the number of incidence and deaths of breast cancer will reach 2.64 million and 1.7 million, respectively, by 2030 if the current morbidity and mortality trend continues. [ 11,12 ] Thus, the development of more effective antibreast cancer agents constitutes a crucial need.…”
Section: Introductionmentioning
confidence: 99%
“…[ 5,6 ] Breast cancer patients initially respond well to chemotherapy, but drug‐resistant breast cancer cells usually readily emerge after long exposure to chemotherapeutics, resulting in treatment failure. [ 7,8 ] Moreover, advanced breast cancer with distant metastases is incurable with currently available chemotherapeutics, [ 9,10 ] and the number of incidence and deaths of breast cancer will reach 2.64 million and 1.7 million, respectively, by 2030 if the current morbidity and mortality trend continues. [ 11,12 ] Thus, the development of more effective antibreast cancer agents constitutes a crucial need.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, patients with mBC face numerous unique challenges that affect their psychological well-being, including coping with uncertainty, feeling out of control, being able to achieve their goals, worrying about death, managing complicated emotions, and balancing hope with realistic expectations for the future. 5,6 In addition to depression, anxiety is quite prevalent among adults with mBC, 7 with estimates ranging from 44% to 61% for clinically significant levels of anxiety. 8 Furthermore, studies have found that higher levels of anxiety and stress can increase the risk patients with mBC have for cognitive decline, which can seriously affect quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Although breast cancer remains the leading cause of female cancer-related death and the median 5-year survival rate for metastatic disease remains low (25%) [ 2 ], earlier detection and advances in oncological treatment have resulted in increasing survival rates [ 3 , 4 ]. Hence, more patients are living with metastatic breast cancer (MBC) and concomitant symptoms of the disease and long-term treatment, such as fatigue, pain, or anxiety [ 5 , 6 ]. As these symptoms contribute to a deterioration of patients’ quality of life (QoL), effective interventions are needed.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure exercise safety and effectiveness, instruction by a trained professional is advisable [ 19 , 20 ], while the content of an exercise program can be designed according to patients’ perceived barriers, facilitators, and preferences to improve exercise adherence. Previous research on this topic has largely been limited to early-stage breast cancer patients [ 21 , 22 ] or mixed cancer types [ 23 26 ], whose needs and preferences may differ from those of patients with MBC [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%